The Correlation Between the DMFT of the 15-year-old Children and the Concentration of Fluoride in Drinking Water from the East Region of the Republic of Macedonia - Ambarkova, Vesna; Kokoceva-Ivanovska, Olga; Stavreva, Natasha; Ambarkov, Jovan; Karakamcev, Tomo (Open Access Macedonian Journal of Medical Sciences, 2022)
AIM: The aim of this study is to determine the correlation between the DMFT index of 15-year-old children from the east region and the concentration of fluoride in drinking water from the populated areas where children live. METHODS: In the examination, 414 children were enrolled, out of seven central secondary schools from four bigger cities from east region, at which the DMFT index was determined. The children live in six different cities and 51 different villages. Fifty-seven water samples were taken from the examined area to determine the fluoride concentration using the electrochemical method using the pH/ISE meter-Thermo-Orion with a special F-electrode (Thermo Orion Ion Plus Fluoride Electrode) at the Institute for public health. Spearman’s method was used to determine the correlation between the specified variables. RESULTS: The total number of children in the examined sample was 414, out of which 226 (54.6%) were male and 188 (45.4%) were female. The prevalence of caries free children was 9.4%. SiC index was 10.22. The average DMFT index in this group of children was 5.77 with a standard deviation of ± 4.02. Maximum concentration of fluorine in drinking water of 0.99 ppmF was determined in the village Raslovci, and 0.87 ppmF in the village Star Karaorman, while the minimum (0.07 ppmF) in the village Dvorishte and (0.10 ppmF) in the village Grad. Correlation of the DMFT index in 15-year-old children from the east region and the concentration of fluorine in the drinking water has a negative, indirect correlation, with the value of the coefficient R = −0.27. CONCLUSION: The correlation between the DMFT index and the concentration of drinking water is a negative, indirect correlation, and statistically, this correlation is highly significant (p < 0.05).